The critical lede: new media and ecological balance - Myers, W. Benjamin; Rowe, Desireé D. (Taylor & Francis, 2012)
As co-hosts of the podcast The Critical Lede (TCL), we find ourselves at a moment where new media projects are bursting onto the scene of not only communication/ performance studies but also all fields of academe. That we find ourselves in the midst of this explosion calls for reflexivity on the potentials that new media projects open as well as problematics that might ensue as we sort out how to keep our traditional print/stage heritage vibrant while simultaneously making room for scholarship that works outside of this framework.
Keywords: Dramatic arts; Media; Theater; Performance art; Critical Lede; Podcasting